MENINGKATKAN KETERAMPILAN MEMBACA BAHASA INGGRIS SISWA MELALUI STRATEGI REPETISI DENGAN CANVA SEBAGAI MEDIA PEMBELAJARAN - Rahma Aini; Bambang Harmanto; Elok Putri Nimasari; Ariyanti Ariyanti (Universitas Muhammadiyah Ponorogo, 2025)
This study aimed to explore how repetition strategies supported by Canva as teaching media could improve students’ English reading skills, particularly their ability to read aloud. The research applied a qualitative approach using the Interpretative Phenomenological Self-Study (IPSS) method combined with the Classroom Action Research (CAR) model proposed by Kemmis and McTaggart. It was conducted in two action cycles with 23 eighth-grade students of SMP Negeri 3 Pulung. Data were collected through observation sheets, affective questionnaires, assessments, and teacher diaries. The focus was on three learning domains: cognitive (reading comprehension), affective (motivation and interest), and psychomotor (reading aloud performance). In Cycle I, the results had not met the expected criteria: cognitive 50%, psychomotor 56.8%, and affective 76.6%. After revising the learning strategy and optimizing Canva media, Cycle II showed significant improvements: cognitive 94%, psychomotor 80.7%, and affective 87.7%. All students successfully exceeded the Minimum Mastery Criteria (MMC). The findings indicated that the integration of repetition strategies with Canva media was effective in improving students’ English reading skills in cognitive, affective, and psychomotor aspects. Moreover, the IPSS approach enabled the researcher to reflect deeply on the teaching experience and adapt the instruction based on students' learning responses.